Daily fortified-synbiotic yogurt consumption facilitates appetite control in overweight and obese adults with metabolic syndrome during a weight-loss program: a 10-week randomized controlled trial - Mohammadi-Sartang, Mohsen; Mazloomi, Seyed Mohammad; Fararouie, Mohammad; Bedeltavana, Alireza; Famouri, Mandana; Mazloom, Zohreh (Progress in Nutrition, 2020)
Objective:Weight loss programm is known to increase the appetite and motivation to eat. The aim of the present study was to compare the effect of fortified-synbiotic yogurt (FSY) with calcium, whey protein and vitamin D with low-fat conventional yogurt (LFY) on appetite control in overweight/obese individuals during weight loss. Method and matrials: This was a randomized, double-blinded, parallel-arm, 10-week study. Participants were randomly allocated to two groups receiving either two servings (2×250 g)/day of a fortified synbiotic yogurt (FSY) with whey protein, calcium, and vitamin D (n=44) or a low-fat conventional yogurt (LFY) (n=43). All participants were put on a caloric-restricted diet throughout the 10-week study. Fasting Visual Analogue Scale (VAS) was used to measure subjective sensations of appetite in before commencing the study, at weeks 5 and 10 of the study. Fasting plasma concentrations of ghrelin were measured as well. Result: Both groups showed a significant (P<0·001) weight loss (-4.3±1.9 kg and -5.12±3.03 kg in the LFY and FSY groups, respectively). A treatment and time×treatment interaction effect indicated that weight loss with FSY induced a smaller increase in desire to eat and hunger and smaller reduction in fullness sensations (P<0.05). Intrisingly, per each kg body fat mass loss during the weight loss, the increase in the desire to eat and hunger as well as decrease in the fullness scores were significanlty lower (P<0.05) in the FSY compared to LFY group. Furthermore, changes in ghrelin concentration correlated with those in desire to eat (r=0.34, P=0.001), hunger (r =0.64, P<0·001) and fullness (r= -0.39, P<0.001) sensations. Although changes in fasting ghrelin concentrations were not significantly diffrerent between groups at the end of the study; the FSY group showed smaller increase in gerlin after 10-weeks study. Conclusions: Collectively, our promising results showed that FSY supplementation attenuates the orexigenic effect of body weight loss compared with LFY and in overweight and obese individuals.